Hubungan Pengetahuan Sikap Dan Tindakan Penggunaan Alat Pelindung Diri Dengan Keluhan Subyektif Karyawan Di Homeindustry Pencelupan Benang - Ni Luh Sri Supia Anggreni; I Made Bulda Mahayana (Poltekkes Kemenkes Denpasar, 2020)
Abstract One of yarn dyeing industries located in Sampalan Klod Village, Dawan district, Klungkung regency, is not optimizing protective private equipment for their employees. The purpose of this study is to determine the correlation of knowledge, demeanor, and behavior regarding the use of personal protective equipment toward subjective complaints of employees in the yarn dyeing industry. The type of research used is descriptive analytic research. The design of this study is cross-sectional using the chi-square test. Based on the results, as much as 53.13% of employees have a moderate level of knowledge. The moderate category of employees’ demeanor was 53.13%. The lack behavior of employees was 37.50%. Yarn dyeing industry's employees who experienced subjective complaints were 56.25%. The test results obtained the results of sig 0,000 which is less than 0.05, which means there is a correlation of demeanor, knowledge, and behavior of protective private equipment of employee's subjective complaints at yarn dyeing home industry. Employees are expected to be able to maintain occupational health and safety work, Health Departments are expected to increase employee knowledge of safety work by routinely providing information about the importance of using personal protective equipment.Keywords: Knowledge, attitudes, actions, subjective complaints